Top-Down Influence Leads to a Reduced Sense of Body Ownership in Individuals With Depersonalization Tendencies: A Focus on Full Body Illusion - Yamamoto, Kazuki; Nakao, Takashi (Frontiers in Psychology, 2022)
Sense of body ownership, that is, the feeling that “my body belongs to me,” has been examined by both the rubber hand illusion (RHI) and full body illusion (FBI). In a study that examined the relationship between RHI and depersonalization, a symptom in which people experience a lower sense of body ownership, people with a high depersonalization tendency experienced RHI through the bottom-up process of visual-tactile integration. Why is it that people with depersonalization feel a lower sense of body ownership over their bodies? Case studies of depersonalization suggest that the top-down cognition in people with depersonalization may make them less likely to feel a sense of body ownership. However, the top-down influence on the sense of body ownership in depersonalization has not yet been experimentally demonstrated. By incorporating top-down manipulation (e.g., instructing participants to regard a fake body as their own) into the FBI procedure, we aimed to clarify the cause of the reduced sense of body ownership in people with a high depersonalization tendency. The FBI procedure was conducted in a virtual reality environment using an avatar as a fake body. The avatar was presented from a third-person perspective, and visual-tactile stimuli were presented to create an illusion. To examine the degree of illusion, we measured the skin conductance responses to the fear stimulus presented after the visual-tactile stimuli presentation. The degree of depersonalization was measured using the Japanese version of the Cambridge Depersonalization Scale. To manipulate the top-down influence, we provided self-association instructions before the presentation of the visual-tactile stimuli. We predicted that the higher the degree of depersonalization, the lower the degree of illusion in the self-association instruction. The results showed that participants with a higher depersonalization tendency had a lower degree of illusion (rho = −0.424, p = 0.035) in the self-association condition. This indicates that in people with a high depersonalization tendency, top-down cognition of the body as their own leads to a decrease in the sense of body ownership.